The End of the Keynesian era : essays on the disintegration of the Keynesian political economy - Skidelsky, Robert; Skidelsky, Robert (London : New York : Macmillan, 1977)
This text is an assembly of a collection of essays whose focus is on the malfunctioning of political economy
Includes index.
ijb, 15/01/2019
Loans
Keywords: Keynesian economics; Economics; Economic history